Teachers' perceptions of portfolio implementation in EFL classes for young language learners : - Trần, Ngọc Bảo Trân (Trường Đại học Cần Thơ, 2018)
This study aimed to determine teachers‟ perceptions of portfolio implementation in young learners‟ classroom regarding their general understanding of portfolios and their perceived advantages as well as disadvantages arising during the process.